Drug Inventory Monitoring System at West Malangke Community Health Center, North Luwu Regency Using Progressive Web Application - Asrul Azhari Muin; Erfina; Marlina Pratiwi (Jurnal INSYPRO (Information System and Processing), 2023)
Monitoring drug supplies at the West Malangke Community Health Center is something that must be done because this drug monitoring function is carried out so that no drugs are missed starting from incoming drugs and outgoing drugs as well as monitoring the expiration of drugs. The process of inputting incoming and outgoing medicines still uses Microsoft Excel, which in the process takes longer because every time a medicine comes in, the officer will record it in the book according to the date of entry of the medicine with more than one type of medicine, then check them one by one, then input them into in Microsoft Excel. Therefore, a system is needed to make it easier for West Malangke Community Health Center pharmacy officers to monitor drug supplies. The monitoring system used is a Progressive Web Application which has responses such as a mobile app, responsive layout, has icons that can be added to the device’s home screen, can send and receive notifications and can simplify the process of monitoring drug supplies in the recording process so that errors do not occur. and the need to pay attention to reporting between receiving and dispensing drugs can produce a good drug monitoring process. Based on research results, the drug supply monitoring system using the Progressive Web Application is very helpful for pharmacy staff in inputting incoming and outgoing drugs as well as helping to monitor drug expiration.